Cheating in Labour Markets - Michalis Drouvelis; Martin G. Kocher (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Our results from a laboratory experiment offer new evidence for the detrimental effects that cheating behaviour in the workplace may have on the degree of reciprocity between firms and workers. First, we replicate existing findings showing that in the absence of monitoring (cheating is possible) workers cheat on their actual performance in a real-effort task. The extent of cheating influences how firms (managers) decide to set their wages in a subsequent gift-exchange game. Specifically, firms offer higher wages to workers who cheat and interestingly, workers expect such behaviour by firms. These higher wages are not matched by workers' performance in the gift-exchange game, where cheating is not possible, resulting in a flat wage-effort relationship. In contrast, in the presence of monitoring (cheating is not possible), we find a positive relationship between wages offered and effort provided by the workers. Our findings have implications for adopting measures at the workplace that eliminate workers' opportunities to cheat on their performance.
Keywords: C72; C91; D21; 330; cheating; gift-exchange; labour market; experiment